Moderate Exercise and Insulin in Combination Protect Against Brain Atrophy and Weight Loss by Modulation of Glucose Metabolism in Rat Model of Alzheimer' Disease - Forough Radfar; Mehdi Shahbazi; Shahzad Tahmasebi Boroujeni; Elaheh Arabameri; Maryam Farahmandfar (Sport Sciences and Health Research)
Background: Alzheimer’s disease (AD), the most prevalent neurodegenerative disorder, is characterized by amyloid-beta (Aβ) plaque accumulation, neurofibrillary tangles, neuronal death, inflammation, and oxidative stress.Aim: We investigated the effects of treadmill exercise and intranasal insulin on spatial memory, blood glucose level, and Physical growth indicators including weight, head circumference, and tail length.Materials and Methods: Seventy-two male Wistar rats, aged 8 weeks were into 9 gtoups at random (control, Sham, Aβ, Aβ + EX, Aβ +PINS, Aβ + INST, Aβ + EX + PINS, Aβ + EX + INST, and Aβ + EX + PINS + INST). We discovered that rats receiving Aβ25-35 had impaired spatial memory, which was associated with weight loss, brain growth retardation, Tail Length, and elevated blood glucose levels. Data from each trial was statistically analyzed using IBM SPSSStatistics 22 software, Two-way ANOVA, and post-hoc analysis Tukey test. The cut-off for statistical significance was P≤0.05.Results: Our results show that the improvement of spatial memory due to the improvement of metabolism and growth indicators can be affected by pretreatment exercise and intranasal insulin. Also, exercise training and intranasal insulin improved spatial memory and prevented brain growth retardation, increased blood glucose, weight loss, and tail length in animals treated with Aβ25-35.Conclusion: Exercise can amplify the positive benefits of intranasal insulin treatment on memory. The results of our research showed that exercise and insulin can prevent brain growth retardation and prevent spatial memory disorders by improving glucose metabolismy.